2014
DOI: 10.1007/s11214-014-0054-6
|View full text |Cite
|
Sign up to set email alerts
|

25 Years of Self-Organized Criticality: Solar and Astrophysics

Abstract: Shortly after the seminal paper "Self-Organized Criticality: An explanation of 1/f noise" by Bak et al. (1987), the idea has been applied to solar physics, in "Avalanches and the Distribution of Solar Flares" by Lu and Hamilton (1991). In the following years, an inspiring cross-fertilization from complexity theory to solar and astrophysics took place, where the SOC concept was initially applied to solar flares, stellar flares, and magnetospheric substorms, and later extended to the radiation belt, the heliosph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
180
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(199 citation statements)
references
References 518 publications
(675 reference statements)
12
180
1
6
Order By: Relevance
“…The presented statistics show that energy dissipation in our model occurs in a form of sporadic spatiotemporal activity bursts which are qualitatively similar to the statistics of solar flares obtained from observations (e.g. Crosby et al 1993;Benz & Krucker 2002;Aschwanden & Freeland 2012;Uritsky et al 2007Uritsky et al , 2013Uritsky & Davila 2014;Aschwanden et al 2016, and references therein). This behavior unfolds over transverse spatial scales of the order of several adjacent flux tubes and represents reconnection events on the misaligned field lines of these tubes.…”
Section: Magnetic Field Spectrumsupporting
confidence: 83%
See 1 more Smart Citation
“…The presented statistics show that energy dissipation in our model occurs in a form of sporadic spatiotemporal activity bursts which are qualitatively similar to the statistics of solar flares obtained from observations (e.g. Crosby et al 1993;Benz & Krucker 2002;Aschwanden & Freeland 2012;Uritsky et al 2007Uritsky et al , 2013Uritsky & Davila 2014;Aschwanden et al 2016, and references therein). This behavior unfolds over transverse spatial scales of the order of several adjacent flux tubes and represents reconnection events on the misaligned field lines of these tubes.…”
Section: Magnetic Field Spectrumsupporting
confidence: 83%
“…Starting with observations of power laws in hard X-ray bursts (Datlowe et al 1974;Dennis 1985), numerous other such power laws have been observed. Solar flare hard X-rays, produced by nonthermal bremsstrahlung from accelerated coronal electrons traveling downwards toward the chomosphere, soft X-ray emission, produced by evaporated chromospheric plasma, and Extreme Ultraviolet (EUV) radiation display power-law frequency distributions in peak flux, energy, and duration (Aschwanden et al 2016, and references therein). Power-law slopes have also been measured in the distributions of solar energetic particle event fluxes (Gabriel & Feynman 1996), radio bursts (Iwai et al 2013;Das et al 1997;Ning et al 2007), and Ellerman bombs (Georgoulis et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Such low-dimensional, conceptual models appear to be very useful in various applications, for example the self-organised criticality model (e.g. Aschwanden et al 2016). The proposed model obviously misses a number of other potentially important effects, in particular, the possibility of the excitation of multiple modes and harmonics.…”
Section: Discussionmentioning
confidence: 99%
“…Этот пространственно-временной скейлинг обычно характеризуется сильными, спадающими по степенному закону корре-ляциями, которые являются типичными для критических явлений [Зеленый, Милованов, 2004]. Как известно, исследования явлений подобного рода объединяются общим назва-нием «самоорганизованная критичность», позиционирующая скейлинговый контекст самоорганизации [Aschwanden et al, 2014].…”
unclassified
“…Смысл СОК -эволюция таких систем к критическому состоянию без настройки каких-либо параметров. Позднее смысл термина критичность был расширен к более общему значению -критической точке [Aschwanden et al, 2014]. Суть СОК состоит в том, что по мере эволюции нелинейной дина-мической системы она неизбежно приближа-ется к критической точке (точке бифуркации).…”
unclassified